2020
DOI: 10.3390/gels6030020
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Nanogels Based on Different Polymeric Moieties for Biomedical Applications

Abstract: Nanogels, or nanostructured hydrogels, are one of the most interesting materials in biomedical engineering. Nanogels are widely used in medical applications, such as in cancer therapy, targeted delivery of proteins, genes and DNAs, and scaffolds in tissue regeneration. One salient feature of nanogels is their tunable responsiveness to external stimuli. In this review, thermosensitive nanogels are discussed, with a focus on moieties in their chemical structure which are responsible for thermosensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 222 publications
0
33
0
Order By: Relevance
“…Furthermore, thermo-responsive polymers can be used as injectable biomaterials in the form of a hydrogel, as shown in Figure 6 [ 205 ]. This allows the in situ formation of scaffolds, minimizing the employment of invasive methods, and representing a novel and advanced drug delivery system especially for subcutaneous application [ 206 , 207 , 208 , 209 ].…”
Section: Drug Delivery Applications Of Bioengineered Thermo-responmentioning
confidence: 99%
“…Furthermore, thermo-responsive polymers can be used as injectable biomaterials in the form of a hydrogel, as shown in Figure 6 [ 205 ]. This allows the in situ formation of scaffolds, minimizing the employment of invasive methods, and representing a novel and advanced drug delivery system especially for subcutaneous application [ 206 , 207 , 208 , 209 ].…”
Section: Drug Delivery Applications Of Bioengineered Thermo-responmentioning
confidence: 99%
“…The fabrication methodology, potential role, and application of nanocarrier-based biomaterials for tissue engineering applications are discussed in Table 1. A recent study suggested that the nanogel-based scaffolds play an effective role in tissue regeneration constructs for tissue engineering applications [124][125][126]. Pullulan-based nanogels were successfully synthesized and two different growth factors, such as human recombinant human bone morphogenetic protein 2 (BMP2) and recombinant human fibroblast growth factor 18 (FGF18), were loaded for effective bone repair in bone tissue engineering.…”
Section: The Potential Role Of Nanocarriers In Tissue Engineeringmentioning
confidence: 99%
“…Thermosensitive micro and nanogels are another type of versatile particles widely employed in stimuli responsive drug release applications [113][114][115][116]. Temperature sensitivity can be steadily imparted through micro and nanogels with various temperature responsive polymers that are included during particle synthesis are p(NIPAM) and poly(N-vinyl caprolactam) (p(NVCL)) as the most commonly used thermosensitive polymers [116,117].…”
Section: Stimuli Responsive Micro/nanogels and Targeted Drug Deliverymentioning
confidence: 99%